The Effectiveness of the Implementation of Exclusive Breastfeeding on the Measurement of Body Weight and Body Length at 6 months of Age as an Effort to Prevent Stunting - Nurqalbi Sampara; Hasriani Saleng (International Journal Of Health Science, 2022)
Breast milk is the main nutrient for babies to protect them against possible disease attacks. The balance of nutrients in breast milk is at its best and the milk is in the best form for the baby's body. The purpose of this study is to deter-mine the effectiveness of the application. The research design used in this study was observational with a prospective cohort approach. Where this research intends to look at several groups based on certain characteristics by taking pur-posive sampling and samples of 30 babies including 15 Exclusive Breastfeeding Groups, 15 Formula Milk Mix Groups, IMD Groups and Formula Milk Mixes in the Work Area of the Bara-Baraya Health Center in 2022. Instru-ments The research used is an observation sheet analyzed using the Chi-Square Fisher Exact test analytical test. Re-search Results There is a significant relationship between Exclusive Breastfeeding, and Mixed Formula Milk to in-crease body weight, and body length. While the results obtained a p value of 0.023 which means there is a significant relationship between the application of exclusive breastfeeding to stunting prevention. In the exclusive breastfeeding group, the stunting rate was lower than those using formula milk, and those who carried out early initiation of breast-feeding according to the standard, which was 1 hour long, tended to give exclusive breastfeeding on demand.